Reducing soil permeability for TPA (Final Disposal Site) using Bacillus subtilis mycobacteria - RIZALDI, RESKA; Ma’ruf , Muhammad Afief (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Abstrack This study evaluates the effectiveness of using Bacillus subtilis bacteria in reducing soil permeability rates in landfill areas. The primary issue faced at landfills is groundwater contamination caused by leachate seepage due to high soil permeability. Conventional approaches, such as using synthetic liners, have limitations, necessitating the development of more sustainable alternative methods. Bacillus subtilis microbacteria were used in this study. The soil inoculated with bacteria underwent an incubation period of 3 days. This study aimed to determine the reduction in permeability values by comparing bacteria-affected soil with untreated soil as a control. SEM testing was conducted to observe the soil structure affected by bacteria after a 3-day incubation period with 15% cementation solution and 5% sand. Bacillus subtilis bacteria were found to reduce soil permeability rates, achieving a result of 1.612x10⁻⁷ for swamp soil with a 15% cementation solution (bacterial reagent) and 5% sand, as well as 9.791x10⁻⁸ for laterite soil with the same cementation solution and sand composition.